Microbiological assessment of laminar flow hoods using broad-spectrum Bacterial and fungal media - Gatimu, R. (2025)
This technical brief describes an experiment conducted at the KEPHIS Plant Quarantine and Biosecurity Station (PQBS) in Nairobi, Kenya, to assess the sterility of laminar flow hoods used in tissue culture laboratories. Two hoods—one fully functional and one recently repaired—were tested using nutrient broth (for bacterial detection) and potato dextrose agar (for fungal detection). Results showed that the repaired hood exhibited bacterial colonies after 24 hours and fungal growth after 36 hours, confirming compromised HEPA filter performance. Routine microbiological testing using broad-spectrum media is recommended for early detection of inefficiencies, ensuring sterility and preventing contamination in micropropagation labs. The study underscores the importance of regular HEPA filter inspection, airflow monitoring, and sterilization verification in maintaining aseptic laboratory environments.